Cancer treatment decision‐making among young adults with lung and colorectal cancer: a comparison with adults in middle age. Issue 9 (2nd September 2015) - Mack, Jennifer W.; Cronin, Angel; Fasciano, Karen; Block, Susan D.; Keating, Nancy L.
Abstract: Objective: Our aim is to understand experiences with treatment decision‐making among young adults with cancer. Methods: We studied patients with lung cancer or colorectal cancer in the Cancer Care Outcomes Research and Surveillance Consortium, a prospective cohort study. We identified 148 young adult patients aged 21–40 years who completed baseline interview questions about cancer treatment decision‐making; each was propensity score matched to three middle adult patients aged 41–60 years, for a cohort of 592 patients. Patients were asked about decision‐making preferences, family involvement in decision‐making, and worries about treatment. An ordinal logistic regression model evaluated factors associated with more treatment worries. Results: Young and middle‐aged adults reported similar decision‐making preferences ( p = 0.80) and roles relative to physicians ( p = 0.36). Although family involvement was similar in the age groups ( p = 0.21), young adults were more likely to have dependent children in the home (60% younger versus 28% middle‐aged adults, p < 0.001). Young adults reported more worries about time away from family ( p = 0.002), and, in unadjusted analyses, more cancer treatment‐related worries (mean number of responses of 'somewhat' or 'very' worried 2.5 for younger versus 2.2 for middle‐aged adults, p = 0.02.) However, in adjusted analyses, worries were associated with the presence of dependent children in the home (odds ratio [OR] 1.55, 95% CI = 1.07–2.24, p = 0.02), rather than age. Conclusions: Young adults involve doctors and family members in decisions at rates similar to middle‐aged adults but experience more worries about time away from family. Patients with dependent children are especially likely to experience worries. Treatment decision‐making strategies should be based on individual preferences and needs rather than age alone. Copyright © 2015 John Wiley & Sons, Ltd.